Latin America, a boiling region. Reconfiguration of regional policy - Ambroggio, Iván (Universidad Nacional de Villa María, 2020)
Latin America is the most unequal region on the planet and has encountered political processes in the last two decades that modified the State´s role in a large part of the region, in the attempts to distribute wealth to achieve levels of equity that were lost decades ago or never achieved, depending on each country. However, most governments which represented these dissimilar processes lost in national elections or were overthrown. In this presentation we will talk about some relevant events in the recent history of Bolivia and Chile and ask about the strategic resources of Latin America and their possible relations with some national and international political movements.